Inspired by Otto...Funny back to the future

The Fibonacci sequence is defined with the recurrence relation f n = f n 1 + f n 2 f_{n} = f_{n-1} + f_{n-2} for n > 2 n>2 with initial terms f 1 = 1 f_1 = 1 , f 2 = 1 f_2 = 1 .

( 1 1 ) + ( 1 2 ) + ( 2 3 ) + ( 3 5 ) + + ( f 2012 f 2013 ) + ( f 2013 f 2014 ) (1 \cdot 1) + (1 \cdot 2) + (2 \cdot 3) + (3 \cdot 5) + \ldots + (f_{2012} \cdot f_{2013}) + (f_ {2013} \cdot f_{2014})

If the value of the expression above equals f n 2 f_n ^2 , find the value of n n .


The answer is 2014.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Kartik Sharma
Oct 25, 2015

n = 1 2013 f n f n + 1 = n = 1 2013 ( f n + 1 f n 1 ) f n + 1 \displaystyle \sum_{n=1}^{2013}{f_n f_{n+1}} = \sum_{n=1}^{2013}{(f_{n+1}-f_{n-1})f_{n+1}}

n = 1 2013 f n + 1 2 f n 1 f n + 1 \displaystyle \sum_{n=1}^{2013}{f_{n+1}^2 - f_{n-1}f_{n+1}}

Lemma : f n f n + 2 = f n + 1 2 + ( 1 ) n \text{Lemma :} f_n f_{n+2} = f_{n+1}^2 + (-1)^n

Using this,

n = 1 2013 f n + 1 2 f n 2 ( 1 ) n \displaystyle \sum_{n=1}^{2013}{f_{n+1}^2 - f_n^2 - (-1)^n}

Now, this easily telescopes to

f 2014 2 1 + 1 = f 2014 2 \displaystyle f_{2014}^2 - 1 + 1 = \boxed{f_{2014}^2}

I cannot think of some really nice proof of the Lemma except using Binet's or Induction. Probably using Q-Matrix, but I don't know.

@Otto Bretscher Can you enlighten me?

Kartik Sharma - 5 years, 7 months ago

f n f n + 2 = f n + 1 2 + ( 1 ) n But f 1 f 3 f 2 2 + ( 1 ) 1 f_n f_{n+2} = f_{n+1}^2 + (-1)^n \\ \text{But } f_{1}f_{3}≠f_{2}^{2}+(-1)^{1}

Akshat Sharda - 5 years, 7 months ago

Log in to reply

I am sorry. But there I am using "pure" Fibonacci numbers where F 0 = F 1 = 1 F_0 = F_1 = 1

Kartik Sharma - 5 years, 7 months ago

Log in to reply

Okay .... it would be better if you had specified it in your solution.

Akshat Sharda - 5 years, 7 months ago

1 1 1 \cdot 1 = 1 2 1^2 = f 1 f 2 f_1 \cdot f_2

1 1 1 \cdot 1 + 1 2 1 \cdot 2 + 2 3 2 \cdot 3 = 3 2 3^2 = f 1 f 2 f_1 \cdot f_2 + f 2 f 3 f_2 \cdot f_3 + f 3 f 4 f_3 \cdot f_4

1 1 1 \cdot 1 + 1 2 1 \cdot 2 + 2 3 2 \cdot 3 + 3 5 3 \cdot 5 + 5 8 5 \cdot 8 = 8 2 8^2 = f 1 f 2 f_1 \cdot f_2 + f 2 f 3 f_2 \cdot f_3 + f 3 f 4 f_3 \cdot f_4 + f 4 f 5 f_4 \cdot f_5 + f 5 f 6 f_5 \cdot f_6

Using induction and seeing the picture above ( 1 1 ) (1 \cdot 1) + ( 1 2 ) (1 \cdot 2) + ( 2 3 ) (2 \cdot 3) + ( 3 5 ) (3 \cdot 5) + ... + ( f 2012 f 2013 ) (f_{2012} \cdot f_{2013}) + ( f 2013 f 2014 ) (f_ {2013} \cdot f_{2014}) = f 2014 2 f^2_{2014} \Rightarrow n=2014

William Isoroku
Oct 26, 2015

The expression is basically:

f 1 ) ( f 2 ) + ( f 2 ) ( f 3 ) + ( f 3 ) ( f 4 ) + . . . . . . ( f 2011 ) ( f 2012 ) + ( f 2012 ) ( f 2013 ) + ( f 2013 ) ( f 2014 ) = f n 2 f_{1})(f_{2})+(f_{2})(f_{3})+(f_{3})(f_{4})+......(f_{2011})(f_{2012})+(f_{2012})(f_{2013})+(f_{2013})(f_{2014})=f^2_{n}

Which factors to;

f 2 ( f 1 + f 3 ) + f 4 ( f 3 + f 5 ) + f 6 ( f 5 + f 7 ) + . . . . . f 2012 ( f 2011 + f 2013 ) + ( f 2013 ) ( f 2014 ) = f n 2 f_{2}(f_{1}+f_{3})+f_{4}(f_{3}+f_{5})+f_{6}(f_{5}+f_{7})+.....f_{2012}(f_{2011}+f_{2013})+(f_{2013})(f_{2014})=f^2_{n}

Based on the definition of Fibonacci sequence, f n = f n 2 + f n 1 f_{n}=f_{n-2}+f_{n-1} ,

We have the related expression

( f 3 f 1 ) ( f 1 + f 3 ) + ( f 5 f 3 ) ( f 3 + f 5 ) + . . . . . . . ( f 2013 f 2011 ) ( f 2011 + f 2013 ) + ( f 2013 ) ( f 2014 ) = f n 2 (f_{3}-f_{1})(f_{1}+f_{3})+(f_{5}-f_{3})(f_{3}+f_{5})+.......(f_{2013}-f_{2011})(f_{2011}+f_{2013})+(f_{2013})(f_{2014})=f^2_{n}

Which equals to:

( f 3 2 f 1 2 ) + ( f 5 2 f 3 2 ) + ( f 7 2 f 5 2 ) + . . . . . . ( f 2013 2 f 2011 2 ) + ( f 2013 ) ( f 2014 ) = f n 2 (f^2_{3}-f^2_{1})+(f^2_{5}-f^2_{3})+(f^2_{7}-f^2_{5})+......(f^2_{2013}-f^2_{2011})+(f_{2013})(f_{2014})=f^2_{n}

All the middle terms cancel out except for the f 2013 2 f^2_{2013} :

f 1 2 + f 2013 2 + ( f 2013 f 2014 ) = f n 2 -f^2_{1}+f^2_{2013}+(f_{2013}*f_{2014})=f^2_{n}

Which equals:

1 + f 2013 ( f 2013 + f 2014 ) = f n 2 -1+f_{2013}(f_{2013}+f_{2014})=f^2_{n}

Which is the same as:

1 + f 2013 ( f 2015 ) = f n 2 -1+f_{2013}(f_{2015})=f^2_{n} (eq.1)

Using the identityof Fibonacci sequence f n + 1 ( f n 1 ) f n 2 = ( 1 ) n f_{n+1}(f_{n-1})-f^2_{n}=(-1)^n and let n = 2014 n=2014 :

f 2013 ( f 2015 ) f 2014 2 = ( 1 ) 2014 = 1 f_{2013}(f_{2015})-f^2_{2014}=(-1)^{2014}=1

Thus f 2013 ( f 2015 ) = 1 + f 2014 2 f_{2013}(f_{2015})=1+f^2_{2014}

Substitute into the original equation:

1 + 1 + f 2014 2 = f n 2 -1+1+f^2_{2014}=f^2_{n}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...